Invisible Sustainability: Decoupling ESG Sustainability Reporting from Tri Hita Karana Practices in Rural Banks in Bali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study investigates the decoupling phenomenon between ESG (Environmental, Social, and Governance) sustainability reporting and communal Tri Hita Karana (THK) sustainability practices in a Rural Bank in Bali. Through Ethnographic Content Analysis (ECA) of official documents from BPR Luhur Damai covering 2023–2025, this study identifies that the Sustainability Report (SR), prepared strictly according to Financial Services Authority Regulation (POJK) 51/2017, does not incorporate substantial THK practices, namely banten (ceremonial offerings) Rp131.6 million, dana punia (religious donations) Rp8.5 million, and monthly banjar (communal community unit) contributions, producing a Hindu religious expenditure to formal Social and Environmental Responsibility (SER) ratio of 10:1. Drawing on the Institutional Logics perspective, this study identifies four decoupling mechanisms: (1) cognitive, namely THK as taken-for-granted, not perceived as “sustainability”; (2) administrative, namely departmental silos between Compliance and General Affairs; (3) template, namely POJK 51/2017 provides no space for local wisdom; and (4) capacity, namely limited Human Resources (HR) and institutional capacity. These findings lead to the concept of “invisible sustainability,” that is, real sustainability contributions that are invisible to conventional reporting frameworks, and “cultural accounting gap,” that is, the absence of accounting categories for local cultural-religious contributions. The theoretical contribution is demonstrating that decoupling in Global South contexts is not merely symbolic compliance but results from structural misalignment between transnational and communal logics that renders local sustainability contributions institutionally invisible.